Interpreting the Tri Mandala Concept on the Motif of Gringsing Wayang Kebo Woven Cloth - Nina Eka Putriani; Sri Marwati; I Wayan Mudra (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2018)
Gringsing wayang kebo woven cloth is one of specialty cloths owned by Tenganan Pegringsingan Village, Manggis Sub-district, Karangasem Regency, Bali. This research aims to interpreting the Tri Mandala concept on the motif of gringsing wayang kebo woven cloth. The approach of this research is descriptive qualitative. Techniques for collecting data are observation, interview, and documentation, data analysis is using interactive analysis model and the validity of the data will be confirmed with triangulation technique. The result of this research shows that the motif of gringsing wayang kebo follows the of Tri Mandala concept that consists of 3 parts, Main pattern, Center pattern, and edge pattern. The motifs consisted of each pattern are 1). The motif on the main pattern consists of the plus, swastika, building, and scorpion motif; 2). The motif on the center pattern consists of an animal motif, floral, mountain, wayang; and; 3). The motif on the edge pattern consists of plus sign (+) and sun.